Recent Technical Advances in Sample Preparation for Single-Particle Cryo-EM - Xu, Yixin; Dang, Shangyu (Frontiers in Molecular Biosciences, 2022)
Cryo-sample preparation, a process with high uncertainty and low reproducibility, is a vital process to obtain high-resolution structures using single-particle cryo-EM method. The existence of air-water interface (AWI) during the sample vitrification process may cause protein denaturation and aggregation, complex disassembly, preferred orientation, and other serious problems of protein particles, which makes it challenging to pursue the high-resolution 3D reconstruction. Therefore, sample preparation has become an important topic with many new methods proposed in different steps trying to solve these problems. In this review, we summarized methods developed to improve quality of cryo-sample in different stages of the sample preparation and provided insights for future strategies developing from different angles. We anticipate the cryo-sample preparation will not be a limited step in single-particle cryo-EM field as more and more approaches developed in near future, which will finally benefit the whole community.